THE INFLUENCE OF THE APPLICATION OF DIGITAL TECHNOLOGY AND ENTREPRENEURIAL ORIENTATION ON MSME PERFORMANCE - Yeti Afrinalita; Nia Nurul Aini; Siska Maya Mein Dewinda; Wiji Mahareni; Siti Aisyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to examine the effect of synergy between the application of digital technology and entrepreneurial orientation on the performance of coffee shop MSMEs in Bojonegoro. The results of the analysis show that the combination of these two variables significantly improves business performance, exceeding the individual impact of each variable. These findings underline the importance of a holistic approach in developing MSMEs in the digital era, which combines technological innovation with. entrepreneurial spirit. The use of technology such as online ordering applications, inventory systems and data analysis allows MSME coffee shops to operate more efficiently, saving time and costs, as well as reducing errors. This research provides important implications for the government and relevant stakeholders to design policies that support the adoption of digital technology by MSMEs such as technology service providers, business consultants and the entrepreneurial community can accelerate the digital transformation process. as well as a more targeted entrepreneurial capacity development program.This research aims to examine the effect of synergy between the application of digital technology and entrepreneurial orientation on the performance of coffee shop MSMEs in Bojonegoro. The results of the analysis show that the combination of these two variables significantly improves business performance, exceeding the individual impact of each variable. These findings underline the importance of a holistic approach in developing MSMEs in the digital era, which combines technological innovation with. entrepreneurial spirit. The use of technology such as online ordering applications, inventory systems and data analysis allows MSME coffee shops to operate more efficiently, saving time and costs, as well as reducing errors. This research provides important implications for the government and relevant stakeholders to design policies that support the adoption of digital technology by MSMEs such as technology service providers, business consultants and the entrepreneurial community can accelerate the digital transformation process. as well as a more targeted entrepreneurial capacity development program.